2011
DOI: 10.2478/v10034-011-0048-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Fanconi's Anemia by Diepoxybutane Analysis in Children from Serbia

Abstract: The high sensitivity of Fanconi’s anemia (FA) cells to drug induced DNA interstrand crosslinks (ICL) such as diepoxybutane (DEB) was used as a part of FA screening in the children with clinical suspicion of FA. The study considered a total of 66 children with the hematological and/or congenital phenotypic symptoms reminiscent of FA. Blood samples from patients with clinical suspicion of FA and controls were collected for chromosome fragility evaluation by the DEB test. According to the results of DEB test, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
4
1
1
Order By: Relevance
“…Our patients' values are comparable with those previously reported in the literatures. Porto et al (2010) noticed that the mean of DEB-induced chromosomal breakage was 7.75 breaks/ cell; however, the results of our study are higher than those of Cirkovic et al (2011) who found that the range of breaks/cell was 0.26-4.39, with a mean breaks/cell 1.37.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our patients' values are comparable with those previously reported in the literatures. Porto et al (2010) noticed that the mean of DEB-induced chromosomal breakage was 7.75 breaks/ cell; however, the results of our study are higher than those of Cirkovic et al (2011) who found that the range of breaks/cell was 0.26-4.39, with a mean breaks/cell 1.37.…”
Section: Discussioncontrasting
confidence: 85%
“…The clinical presentation of our patients, hematological abnormalities, and clinical features are well characterized for the disease and did not differ from those reported in the literature (D'Andrea, 2010;Cirkovic et al, 2011;Alter and Kupfer, 2013). In addition, in this study, we could not detect any correlation between the sensitivity to the DEB or the corrective value of the adult or cord blood and the severity of the condition as shown by their complete blood count profile or the number of the anomalies present in patients.…”
Section: Figurementioning
confidence: 37%
“…Again a large cohort study applied flow-based MMC sensitivity test to evaluate FA phenotype in fibroblasts [20]. A study in Serbia was performed on FA-affected children and found the percentage of DNA cross-linker-induced aberrant cells was increased more than 26 times in FA patients compared to non-FA patients [22]. This study also supports this observation of DNA cross-linker-induced chromosomal breakage is very high in FA patients.…”
Section: Discussionsupporting
confidence: 65%
“…FA is an autosomal recessive chromosomal instability syndrome characterized by congenital abnormalities, progressive bone marrow failure and cancer predisposition. It has already been documented in various literatures that the gold standard diagnostic test for FA consists of cytogenetic quantitation of chromosomal breakage in response to DNA cross-linking agents like diepoxybutane (DEB) or MMC [13][14][15][16][17][18][19][20][21][22]. We have already mentioned the detailed protocol of stress cytogenetics in Section 2.…”
Section: Discussionmentioning
confidence: 99%
“…Fanconi anemia cells are hypersensible to the clastogenic effect of DEB compared with non-Fanconi anemia control cells [Auerbach, 2015]. The 0.1 μg/ml final concentration of DEB (equivalent to ∼ 1.16 μ M ) is widely used for Fanconi anemia diagnostic testing because it induces chromosomal damage without affecting the mitotic index [Auerbach, 1988[Auerbach, , 2003[Auerbach, , 2009[Auerbach, , 2015Auerbach et al, 1989;Seyschab et al, 1995;Howell, 2001;Castella et al, 2011;Cirkovic et al, 2011; our own laboratory experience]. In addition, an effect on cell viability by DEB has been demonstrated to occur at concentrations severalfold higher than 0.1 μg/ml [Costa et al, 1997;Ruppitsch et al, 1998;Vock et al, 1999;Ponte et al, 2011;Fabiani et al, 2012].…”
Section: Introductionmentioning
confidence: 99%